CHARACTERIZATION OF ALKALINE PROTEASE FROM BACILLUS CEREUS STRAIN S8 BY INSILICO APPROACH - Lakshmi B.K.M1*, Muthyam Sowjanya2, Muni kumar D3, Ch.Venkatrayulu4; Hemalatha H.P.J5 (Chelonian Research Foundation, 2023)
Proteases are the hydrolytic enzymes which catalyzes hydrolysis of proteins and one of the most prominent group of enzymes that find potential uses in various industrial sectors. Scientists have been trying continuously to introduce the enzymatic methods instead of chemical processes to promote the ecofriendly environment. The present study aims to carry such superior alkaline protease (APBCS8) insilico characterization from Bacillus cereus strain S8 (APBCS8) as deducing its unique three dimensional (3D) native structure is a daunting task. It contains 208 amino acids. Conserved domain, motif scan results and phylogenetic tree analysis of APBCS8 revealed that it belongs to Beta-lactamase family and transpeptidase super family. Three dimensional structure of APBCS8 was predicted by using LOMETS, a threading based structure prediction method. The modeled secondary structure of protease contains 3 beta sheets, 4 beta hairpins, 1 beta bulge, 9 strands, 10 helices, 9 helix helix interacs, 17 beta turns and 2 gamma turns. Assessment and authentication results from Ramachandran plot analysis by PROCHECK showed that alkaline protease from Bacillus cereus strain S8 (APBCS8) is of good quality. Active site of APBCS8 was predicted using COACH to predict ligand binding sites using the BioLiP database and demonstrated that this protease is a serine protease, probably mediates its mechanism of action through catalytic triad (Histidine, Aspartic acid, Serine). Interaction of APBCS8 with set of proteins is studied by using STRING database. It can be concluded that structural characterization of enzymes by bioinformatic tools might be fruitful in predicting their novel properties by studying at their gene level. Key Words: Alkaline protease APBCS8, LOMETS, Three dimensional structure, COACH, STRING.